The Literary Life and Correspondence of the Countess of Blessington, Volume 3 - Madden, Richard Robert (Cambridge library collection. Literary Studies, 1855)
Following her advantageous second marriage, the famous beauty Marguerite, Countess of Blessington (1789–1849), presided over one of London's most glittering salons, variously attended by Thomas Moore, Disraeli, Bulwer Lytton, and Dickens. After her husband's death in 1829, she augmented her income by writing, most notably her Conversations with Lord Byron, which recounted her acquaintance with the poet in Genoa. Despite considerable success, her debt-ridden establishment collapsed in 1849 and Lady Blessington fled to Paris, where she died. This 1855 biography and letters, in three volumes was edited by R. R. Madden (1798–1886), colonial administrator and Fellow of the Royal College of Surgeons, who had first met the Blessingtons in Naples in 1821. It illuminates the intriguing social role of the salon hostess and its many financial and emotional pressures. Volume 3 contains further brief biographies of her various correspondents, followed by their letters